Optical spectroscopy of X-mega targets in the Carina nebula : VI. FO 15: A new O-type double-lined eclipsing binary - Niemelä, Virpi Sinikka (2006)
We report the discovery of a new O-type double-lined spectroscopic binary with a short orbital period of 1.4 d. We find the primary component of this binary, FO 15, to have an approximate spectral type O5.5Vz, i.e. a zero-age main-sequence (ZAMS) star. The secondary appears to be of spectral type O9.5V. We have performed a numerical model fit to the public All Sky Automated Survey photometry, which shows that FO 15 is also an eclipsing binary. We find an orbital inclination of ∼80°. From a simultaneous light curve and radial velocity solution, we find the masses and radii of the two components to be 30 ± 1 and 16 ± 1 M⊙ and 7.5 ± 0.5 and 5.3 ± 0.5 R⊙. These radii, and hence also the luminosities, are smaller than those of normal O-type stars, but similar to recently born ZAMS O-type stars. The absolute magnitudes derived from our analysis locate FO 15 at the same distance as η Carinæ. From Chandra and XMM X-ray images, we also find that there are two close X-ray sources: one coincident with FO 15 and the other one without optical counterpart. The latter seems to be a highly variable source, presumably due to a pre-main-sequence stellar neighbour of FO 15.